Bacterial inactivation of liquid food and water using high‐intensity alternate electric field. Issue 4 (18th November 2016) - Peng, Peng; Cheng, Yanling; Song, Hao; Zhang, Tingting; Deng, Shaobo; Anderson, Erik; Addy, Min; Zhu, Xindi; Liu, Shiyu; Hatzenbeller, Raymond; Li, Yun; Lin, Xiangyang; et al.
Abstract: Bacteria contaminated liquid food and water, along with the harmful byproducts from chemical disinfection methods, raise concerns to the public health. This article investigated the inactivation of bacteria in liquid food and water using the pilot‐scale concentrated high intensity electric field (CHIEF) system. By generating a strong alternate electric field in a small region of the reactor, the pilot CHIEF system was able to inactivate microbes at a continuous operation. Compared with other disinfection methods, the CHIEF system used relatively less energy density to decontaminate and required a shorter treatment time. The mildest energy density required was 500 kJ/L to obtain a 5‐log reduction for Escherichia coli, at the minimum treatment time of 4.7 ms. An electric field analysis was performed using both an equivalent‐circuit model and numerical simulation. A logarithm function model and a Weibull model were used to describe the effects of energy density and treatment time on the disinfection effectiveness of the CHIEF system. The CHIEF system was compared with other water disinfection methods in multiple aspects, such as treatment time and energy consumption. Practical applications: The concentrated high intensity electric field (CHIEF) process presented in this study is a continuous process that can be used to decontaminate liquid food or water. The process operates under non‐thermal conditions, which protects the nutrient and flavor of the food. The process uses alternate electric supply at a relatively low voltage (≤ 10 kV) and frequency (60 Hz). The reactor design and material selection enable a strong electric field to form within the treatment region, allowing the inactivation of microbes without using the pulsed energy. As a result, the process can achieve effective decontamination under a relatively short treatment time (4.7 ms) and moderate energy cost (500 kJ/L). Since the process eliminates the use of pulse generators, it requires less capital investment and has more scale‐up potentials.